Cervical Epidural Analgesia in Current Anaesthesia Practice: Systematic Review of Its Clinical Utility and Rationale, and Technical Considerations. Issue 6 (December 2016) - Shanthanna, H.; Mendis, N.; Goel, A.
Abstract : (Abstracted from Br J Anaesth, 116(2):192–207, 2016) Cervical epidural analgesia (CEA) is an analgesic technique involving the administration of local anesthetics into the epidural space, resulting in the blockade of cervical nerve roots. Cervical epidural analgesia is potentially useful for surgeries involving the upper body.